Identifying and Ranking the Factors Influencing the Performance of Human Resources in Mostazafan Foundation Using Fuzzy Delphi-AHP and BSC Methods - Morvarid Shojaie; Toraj Mojibi; Ali Mehdizadeh Ashrafi (Discrete Dynamics in Nature and Society)
The presented study evaluates the performance with the balanced scorecard approach and fuzzy Delphi in the Mostazafan Foundation. The main goal of the present study is to consider the most important key indicators of human resource performance for designing a business dashboard based on multi-criteria decision-making in the Mostazafan Foundation. For this, the main contributions of the article are (1) identifying the main effective human resource performance indicators using the Delphi method and (2) presenting an integration framework using multi-criteria decision-making according to the determined indicators. The target population of the study was the senior and middle managers of the Mostazafan Foundation. The questionnaire was completed by 30 experts and Cronbach’s coefficient for the questionnaire was calculated to be 0.87. Finally, after using the fuzzy Delphi method, the key indicators for evaluating the performance of the Mostazafan Foundation were obtained and ranked using AHP. The results show the ranking of indicators from the financial perspective: the organization’s profit per employee (per capita profit), the organization’s income per employee (per capita income), and the cost of compensation for total services per employee; from the customer’s point of view: the level of commitment and belonging of employees to the organization; the client’s complaint rate and employees’ perceptions of using their capabilities in the organization; in terms of internal processes: agility in hiring the right staff, key employees by market standards; and in terms of growth and learning, the percentage of key employees with a development plan, the rate of staff with a coach, and the rate of trained staff.